Molecular mimicry of SARS-COV-2 antigens as a possible natural anti-cancer preventive immunization - Ragone, Concetta; Mauriello, Angela; Cavalluzzo, Beatrice; Cavalcanti, Ernesta; Russo, Luigi; Manolio, Carmen; Mangano, Simona; Cembrola, Biancamaria; Tagliamonte, Maria; Buonaguro, Luigi (Frontiers in Immunology, 2024)
In the present study we investigated whether peptides derived from the entire SARS-CoV-2 proteome share homology to TAAs (tumor-associated antigens) and cross-reactive CD8+ T cell can be elicited by the BNT162b2 preventive vaccine or the SARS-CoV-2 natural infection.Viral epitopes with high affinity (<100nM) to the HLA-A*02:01 allele were predicted. Shared and variant-specific epitopes were identified. Significant homologies in amino acidic sequence have been found between SARS-CoV-2 peptides and multiple TAAs, mainly associated with breast, liver, melanoma and colon cancers. The molecular mimicry of the viral epitopes and the TAAs was found in all viral proteins, mostly the Orf 1ab and the Spike, which is included in the BNT162b2 vaccine.Predicted structural similarities confirmed the sequence homology and comparable patterns of contact with both HLA and TCR α and β chains were observed. CD8+ T cell clones cross-reactive with the paired peptides have been found by MHC class l-dextramer staining.Our results show for the first time that several SARS-COV-2 antigens are highly homologous to TAAs and cross-reactive T cells are identified in infected and BNT162b2 preventive vaccinated individuals. The implication would be that the SARS-Cov-2 pandemic could represent a natural preventive immunization for breast, liver, melanoma and colon cancers. In the coming years, realworld evidences will provide the final proof for such immunological experimental evidence.Moreover, such SARS-CoV-2 epitopes can be used to develop "multi-cancer" off-the-shelf preventive/therapeutic vaccine formulations, with higher antigenicity and immunogenicity than over-expressed tumor self-antigens, for the potential valuable benefit of thousands of cancer patients around the World.